PEMBELAJARAN BERBASIS PROYEK PADA PEMBUATAN FACE TONER KEFIR BERAS MERAH (Oryza nivara) UNTUK MENGEMBANGKAN KINERJA ILMIAH - Akila, Febiyuniesa Noorwahnov; Windayani, Neneng; Sundari, Citra Deliana Dewi; Sukmawardani, Yulia (Lantanida Journal, 2025)
This study aims to describe the project-based learning process in developing students' scientific performance with the help of project-based worksheets in making red rice kefir face toner (Oryza nivara), as well as analyzing the characteristics of the resulting face toner product. The method used was a pre-experimental design with a One-Shot Case Study, involving three groups of Grade XI Industrial Pharmacy students, using instruments validated by two experts in Chemistry Education and one vocational school teacher. The results showed that students' activities during the learning process achieved an average score of 92.4, and their scientific performance demonstrated significant improvement with an average score of 94.2, both falling into the “very good” category. Analysis of the product characteristics showed that all formulations of red rice kefir face toner (Oryza nivara) met SNI standards with good quality based on organoleptic parameters, pH, homogeneity, moisture content, and irritation, and the product received an average score of 97.5, categorized as excellent. Additionally, the IC50 value obtained was 73.13 ppm, indicating that this face toner has sufficiently strong antioxidant activity. These results demonstrate that project-based learning with the assistance of project-based worksheets is effective in developing students' scientific performance and producing innovative products.